2021
DOI: 10.7717/peerj.11377
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis based on DNA methylation and RNA-seq reveals hypermethylation of the up-regulated WT1 gene with potential mechanisms in PAM50 subtypes of breast cancer

Abstract: Background Breast cancer (BC), one of the most widespread cancers worldwide, caused the deaths of more than 600,000 women in 2018, accounting for about 15% of all cancer-associated deaths in women that year. In this study, we aimed to discover potential prognostic biomarkers and explore their molecular mechanisms in different BC subtypes using DNA methylation and RNA-seq. Methods We downloaded the DNA methylation datasets and the RNA expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…Cen et al found a significant decrease in proliferation of COAD cells after knocking down IGFL2-AS1 43 . In some database-based studies, IGFL2 was found as a potential pathogenic gene or gene affecting prognosis in liver, breast, renal clear cell, and bladder cancers [44][45][46][47] , which is consistent with the results of our analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Cen et al found a significant decrease in proliferation of COAD cells after knocking down IGFL2-AS1 43 . In some database-based studies, IGFL2 was found as a potential pathogenic gene or gene affecting prognosis in liver, breast, renal clear cell, and bladder cancers [44][45][46][47] , which is consistent with the results of our analysis.…”
Section: Discussionsupporting
confidence: 92%
“…MYC was also found to co-amplify with PVT1 in several cancer cell lines. CD300LG has a functional dependency associated with WT1 , and upregulation and hypermethylation of WT1 have been associated with poor prognosis ( Ren et al, 2021 ). CD300LG also has a wide variety of immunological functions ( Borrego, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…73 Moreover, COL11A1 is selected as the N6-methyladenosine (m6A) target gene and the downstream gene of Wilms tumor gene 1 (WT1). 74,75 Its regulation is involved in miR-29, 76 TGF-β1 signaling, 77 AKT/c/EBPβ/PDK1 axis 78 and other collagens, such as collagen type XI alpha 2 (COL11A2), collagen type XI alpha 3 (COL11A3), collagen type V alpha 1 (COL5A1) and collagen type V alpha 2 (COL5A2). Additionally, COL11A1 is observed to be upregulated in recurrent tumors, promoting tumor recurrence post chemotherapy.…”
Section: Collagen Type XI Alpha 1 Chain (Col11a1)mentioning
confidence: 99%